Under-pricing and listing board in explaining heterogeneity of opinion regarding values of Malaysian IPOs - Othman Yong,; Ali Albada, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Heterogeneity of opinion regarding the value of an initial public offering (IPO) is arguably high due to the lack of prior information on the IPO. This situation is especially true in the case of a fixed-price IPO where, unlike book-building and auction offering methods, potential investors do not have the opportunity to “reveal” their private valuations of the IPO. Using a sample of 112 fixed-price Malaysian IPOs from January 2009 to December 2015, and employing OLS regression together with stepwise regression and hierarchical multiple regression, the objective of this study is to examine the level of under-pricing as the main factor that can possibly explain the heterogeneity of opinion among investors regarding the true value of a fixed-price IPO. The study found that the level of under-pricing, together with control variable ACE Market versus Main Market can explain 50.7 percent of the variation in the heterogeneity of opinion regarding the value of Malaysian fixed-price IPOs. The novelty of this study as opposed to an earlier study by Low and Yong (2013) is in terms of the more rigorous method employed in the form of not just the OLS, but also the stepwise and the hierarchical multiple regressions. This study also offered an improved model with higher R2. The results have some policy implications for the regulatory bodies of Bursa Malaysia in terms of special attention to IPOs listed on the ACE market due to their high initial return and price spread which could be due to excessive speculation.